KTPUNTUKAHOK: THE ROLE OF SOCIAL MEDIA AS A TOOL OF SOCIAL MOVEMENT - Sinaga, Margaretha (PEOPLE: International Journal of Social Sciences, 2015)
In 2017, there is going to be a governor election in province with the highest population density in Indonesia, Jakarta Capital Region. This upcoming general election highlights a number of subject matters, the most evident of which is the aggregation of 1 million Indonesian identity card for a future governor candidate, Basuki Tjahaja Purnama also known as Ahok. Ahok is now no longer carried by a political party. On behalf of being a future governor candidate, referring to Peraturan KPU No. 9 Tahun 2015, he needs propulsion from at least 750.000 Jakarta inhabitans. To make it exactly safe, Ahok needs 1 million copies of ID card of his supporters, and ought to be collected on July 2016 as the governor election will be held on February 2017. Volunteers who support Ahok are named “Teman Ahok” (Ahok’s Friends). They are making bombard in social media with hash tag #KTP untuk Ahok (ID card for Ahok) and producing a 2- minute-47-second video published in YouTube, entitled “Satu Juta KTPuntuk Ahok”. This way of social media bombarding aims to inform people as well as forming mass mobilization about Ahok and the plan, well be said to make social movement. This study describes the role of social media as a tool of social movement.